The Contribution of Reading Interest and Internet Addiction to Undergraduate Students' Critical Thinking Skills in an Indonesian Public University - Pujiastuti, Indah; Lestari, Dian; Damaianti, Vismaia S; Mulyati, Yeti; Sastromiharjo, Andoyo (Universitas Negeri Makassar, 2025)
This study examines the relationship among undergraduate students' interest in reading academic texts, internet addiction, and critical thinking abilities. Additionally, it aims to elucidate how much interest in reading academic texts and internet addiction influence students' critical thinking skills. This investigation implements a correlational research design. The data were gathered through questionnaires and tests administered to undergraduate students enrolled in the Pendidikan Bahasa dan Sastra Indonesia (PBSI) Program at Maritim Raja Ali Haji University (UMRAH). The results were analyzed using multiple and partial correlations to assess the effects of interest in reading academic texts and internet addiction on students' critical thinking skills. The key findings are presented as follows: There exists a significant moderate correlation among interest in reading academic texts, internet addiction, and students' critical thinking skills; Interest in reading academic texts positively correlates with critical thinking skills, indicating that greater interest in reading corresponds to stronger critical thinking skills, and vice versa; Internet addiction negatively correlates with students' critical thinking skills, suggesting that increased addiction is linked to lower critical thinking abilities. Both interest in reading academic texts and internet addiction contribute to students' critical thinking skills, with internet addiction contributing more to critical thinking skills than students' reading interest. This study successfully demonstrated a significant moderate correlation between interest in reading academic texts, internet addiction, and critical thinking skills among students because Sig. Fcount < ρ-value in line with the theory that the intensity of academic literacy engagement and external factors, such as internet use, influences critical thinking skills.